Analisis Efisiensi Penggunaan Tempat Tidur di Rs Elisabeth Medan Per Ruangan Berdasarkan Indikator Rawat Inap di Triwulan 1 Tahun 2022 - Wetty mayanora Mendrofa; Angelia Pasaribu (Yayasan Literasi Sains Indonesia, 2022)
Inpatient services may have an effect on the level of efficiency in the hospital which is wrong in the inpatient indicator that is BOR, ALOS, TOI, and BTO that have not comply with MOH standard. To analyze the wealth of using the bedroom at RS ELISABETH MEDAN. This type of research is descriptive . Document study instrument review guide (daily census of inpatient in the journal). The results showed that the value of BOR, ALOS, TOI, and BTO was high enough to exceed the ideal rate according to Manistry of Health, highest BOR in Elisabeth Medan with BOR value 98%, lowest BOR in Melania room with 76.8%, TOI highest in room and Mari-Marta room with value 12,76%, lowest TOI value in room Shanto Yosef with value 1,13%. The conclusions used by many outdoor beds in accordance with the Manistry of Health were given the results of the overall BOR room 81.18 according to the Manistry of health Standard 60-85%. ALOS value 86.125% whereas According to Ministry of Health Standard 6- 9 days, BTO Value 12.7river on According to Ministry of Health Standard 40-50 times and value of TOI 7.99 days According to Standard Depkes 1-3 days. Divide To the officer to improve the quality of service to patient.